2003
DOI: 10.1540/jsmr.39.119
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Properties of Inhibitory Junction Potential in Murine Lower Oesophageal Sphincter.

Abstract: The electrophysiological properties of smooth muscle in the murine lower oesophageal sphincter (LOS) were investigated by intracellular microelectrode recording. Inhibitory junction potentials (IJPs) evoked by trains of field stimulation (30 V, 0.2-0.3 ms, 10 stimuli at 1-50 Hz) were observed in the murine LOS in the presence of atropine (1 µM) and nifedipine (1 µM). The IJP consists of two components, which we termed fast IJP and slow IJP. The fast IJP was partly sensitive to guanethidine (5 µM), pyridoxalpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
4
9
0
Order By: Relevance
“…Our results on pigs show that maximal EFS relaxation was inhibited to the same degree by L-NAME and ODQ (by 60%) and that apamin fully blocked the EFS induced relaxation resistant to nitric oxide inhibition in both series of experiments. The apamin-sensitive component has been indirectly attributed to ATP in previous studies (Imaeda and Cunnane, 2003). We found that the apamin-sensitive component of EFS relaxation is strongly inhibited by MRS 2179, showing that a purine mediates this component by acting on P2Y 1 receptors; it is slightly but consistently inhibited by NF 279, also suggesting the involvement of P2X 1,2,3 receptors; and it is slightly inhibited by the peptidase chymotrypsin, suggesting that PACAP (an apamin-sensitive peptidergic neurotransmitters) also has a minor role in EFS-induced relaxation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our results on pigs show that maximal EFS relaxation was inhibited to the same degree by L-NAME and ODQ (by 60%) and that apamin fully blocked the EFS induced relaxation resistant to nitric oxide inhibition in both series of experiments. The apamin-sensitive component has been indirectly attributed to ATP in previous studies (Imaeda and Cunnane, 2003). We found that the apamin-sensitive component of EFS relaxation is strongly inhibited by MRS 2179, showing that a purine mediates this component by acting on P2Y 1 receptors; it is slightly but consistently inhibited by NF 279, also suggesting the involvement of P2X 1,2,3 receptors; and it is slightly inhibited by the peptidase chymotrypsin, suggesting that PACAP (an apamin-sensitive peptidergic neurotransmitters) also has a minor role in EFS-induced relaxation.…”
Section: Discussionmentioning
confidence: 91%
“…Colocalization of these neurotransmitters and/or their synthesizing enzymes on inhibitory enteric motor neurons of the upper gastrointestinal tract including LES has been described by immunohistological and other morphological studies (Ny et al, 1994(Ny et al, , 1995aUc et al, 1997;Werkstrom et al, 1997). Physiological and pharmacological studies have demonstrated the direct effects or characterized the actions of these neurotransmitters after stimulation of inhibitory LES motor neurons (Ny et al, 1995bUc et al, 1997;Yuan et al, 1998;Imaeda and Cunnane, 2003). However, evidence suggests that nitric oxide from neural sources is the major contributor to LES relaxation (Murray et al, 1991;Tottrup et al, 1991;Gonzalez et al, 2004), and the relative physiological contribution of other neurotransmitters remains unclear.…”
mentioning
confidence: 99%
“…The fast component presents a rundown, whereas the slow component can be sustained (10). In the clasp region of the mouse (14,41), IJP also has a fast component partly antagonized by apamin, followed by a slow sustained nitrergic component. In the present study, we could not record a biphasic IJP, and the response in strips obtained from both the EB and the clasp and sling regions in the LES showed only a slow component with a small amplitude (5-6 mV), which was L-NNA sensitive and could be sustained under repetitive stimulation.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, these two muscles demonstrate differences in resting membrane potential, voltage-gated K ϩ and Ca 2ϩ channel current densities, and calcium handling (28, 29, 43). These differences provide for the likelihood that neural mediation of relaxation as well as maintenance of resting tone would also differ in sling and circular muscles.The inhibitory neurotransmitter nitric oxide (NO) relaxes the circular muscle in virtually all species studied (7,16,31,39,48,(52)(53)(54). There is little or no evidence that the sling muscle is innervated by or responsive to nitrergic influence.…”
mentioning
confidence: 99%
“…The inhibitory neurotransmitter nitric oxide (NO) relaxes the circular muscle in virtually all species studied (7,16,31,39,48,(52)(53)(54). There is little or no evidence that the sling muscle is innervated by or responsive to nitrergic influence.…”
mentioning
confidence: 99%